2023
DOI: 10.55563/clinexprheumatol/255qsx
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren's syndrome: one year in review 2023

Simone Longhino,
Loukas G. Chatzis,
Roberto Dal Pozzolo
et al.

Abstract: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disorder characterised by the T-cell-mediated hyperactivation of B-cells and cytokine production. The condition may evolve from an asymptomatic, indolent course, with glandular involvement, to extraglandular systemic manifestations up to lymphoma development. On tissue level, the typical feature is the lymphocytic infiltration of the salivary gland by B-, T-and antigen presenting cells, as mirrored by the diagnostic cornerstone role of minor salivary gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Several studies have shown that an increase in local salt concentration caused CD4+ T cell differentiation into Th17 [29,30] and the development of autoimmune diseases [30,31]. Although the biological mechanisms leading to SS sicca symptoms are poorly understood, increasing evidence suggests that dryness of the eyes and mouth are not only the result of SG destruction but primarily the consequences of cytokine, autoantibody, and soluble factor production exacerbating the pathological inflammatory process [3,5,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that an increase in local salt concentration caused CD4+ T cell differentiation into Th17 [29,30] and the development of autoimmune diseases [30,31]. Although the biological mechanisms leading to SS sicca symptoms are poorly understood, increasing evidence suggests that dryness of the eyes and mouth are not only the result of SG destruction but primarily the consequences of cytokine, autoantibody, and soluble factor production exacerbating the pathological inflammatory process [3,5,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Sjogren’s syndrome (SS) is an autoimmune disorder that manifests as dryness of the eyes and mouth accompanied by lymphocytic infiltrates in the lacrimal and salivary glands. This chronic condition, categorized as primary (pSS) or secondary SS, is often linked to other rheumatic diseases and presents with extraglandular manifestations across various systems [ 1 ]. The diagnosis of SS relies on a combination of clinical, serological, and functional tests and histopathological biomarkers based on the 2016 American College of Rheumatology/European Alliance of Associations for Rheumatology (ACR/EULAR) classification criteria [ 2 ].…”
Section: Introductionmentioning
confidence: 99%